'An Unco Sound': On Translating 'Tam o' Shanter' into Spanish. Issue 1 (March 2022) - Llaza, Carlos
Abstract : Robert Burns's 'Tam o' Shanter' remained practically unknown in Spain and Hispanic America until 1954. Since then, it has been included in every volume of Burns's poetry translated into Spanish. Moreover, in the twentieth-first century, renderings of Burns's 'wild ride' can be found in niche media ranging from a paganism website and an Iron Maiden fansite to a blog about single-malt. Given the challenges presented by Burns's poem, translators have achieved uneven results. This essay thus explores the previous translations of 'Tam o' Shanter' into Spanish, questioning the possibilities of poetry translation, in order to present a new rendering.